Clínica San Gabriel nivel tres en el municipio de Girardot, Cundinamarca (2024)
The lack of high-complexity medical centers in the municipality of Girardot, Cundinamarca, has led to high mortality rates from circulatory system diseases and other complex pathologies. Therefore, it is proposed to design a level three clinic that offers specialized care and reduces the dependency on transfers to distant medical centers. The project aims not only to improve the quality of life and health of Girardot's residents but also to boost the local economy by reducing costs associated with traveling to far-off medical facilities. Additionally, it seeks to promote medical tourism by offering specialized services to patients from other municipalities.